Examining the Relationship between Earnings and Patent Filings among Pharmaceutical Companies in Asia - Alina Okun; Randall Valentine (International Journal of Economics and Financial Issues, 2020)
Asian pharmaceutical firms often take over a decade to develop new patentable technology, with costs running into billions of dollars. It is a widely held belief that the resulting patents determine the future viability of the firm. The purpose of this study is to examine the number of patent filings and the number of jurisdictional patent filings on the earnings of the firm. We find that a significant relationship exists between the number of patent filings and profitability, but no such relationship exists between the jurisdictional filings and profitability. Keywords: Pharmaceutical, Patent Filing, Asian Health Care JEL Classifications: F, G, M DOI: https://doi.org/10.32479/ijefi.10509